Physicochemical properties of alginate-based films: effect of ionic crosslinking and mannuronic and guluronic acid ratio - Costa, Maria J. (2018)
Abstract The use of alginates as films in food applications has increased in the recent years due to their swelling capacity and overall functionality. This behaviour is a result of their capacity to crosslink with Ca2+ ion. Aiming to fully understand the effect of calcium chloride (CaCl2) crosslinking and the mannuronic (M) and guluronic (G) acid ratio (M/G) of alginate structure in the films properties, alginate-based films with different (M/G) ratios were crosslinked at increasing CaCl2 concentrations. Films were produced by casting, and characterized in terms of mechanical properties (tensile strength and elongation-at-break), opacity, water sensitivity (moisture content, solubility and water vapour permeability) and morphology, evaluated by scanning electronic microscopy (SEM). Chemical interactions were studied by Fourier Transform Infrared Spectroscopy (FTIR) to assess possible chemical modifications of alginate-based films after crosslinking. Crosslinking significantly affected the alginate structure and properties, decreasing film thickness, moisture content, solubility and water vapour permeability of the alginate-based films. The mechanical properties were also influenced by the crosslinking and high CaCl2 concentrations lead to an increase of tensile strength. Results showed a relation between M/G ratios and CaCl2 concentrations and the resulting films properties. Alginate and the respective crosslinker should be chosen taking into account M/G ratio, since high contents of M residues lead to fragile and flexible films and high content of G residues to stronger films, and these properties are highly dependent on the concentration of CaCl2. Overall, alginate-based films are a good candidate to obtain tailored made edible films for food applications. Further investigation should be done to fully understand the effect of the alginate chain composition and order (e.g. MM, GG, GM, MG) in alginate-based films properties.